Beyond devices: preschoolers’ learning behaviors as moderators of the link between home digital resources and their digital literacy - Moon, Young Kyung (Frontiers in Psychology, 2025)
This study investigated how preschoolers’ learning behaviors moderate the relationship between home digital resources and their digital literacy. Digital literacy was conceptualized in two domains: operational digital literacy, which involve the ability to manipulate digital devices, and cultural digital literacy, which emphasize creative engagement and meaning-making. Participants included 514 preschool-aged children and their mothers in South Korea. Mothers reported on home digital resources and children’s learning behaviors, while validated scales were used to assess operational and cultural digital literacy. Moderation analyses tested whether competence motivation, attention/persistence, and learning strategy influenced the strength of the relationship between digital access and literacy outcomes. The results showed that access to home digital resources significantly predicted both operational and cultural digital literacy. For operational digital literacy, competence motivation and learning strategy strengthened the effect of digital access, suggesting that motivated and strategically engaged children gained greater technical benefits. Attention/persistence, however, did not moderate this relationship. For cultural digital literacy, competence motivation again acted as a positive moderator, indicating that motivated children engaged more deeply with symbolic and creative aspects of digital media. In contrast, learning strategy unexpectedly weakened the relationship, suggesting that children with less structured approaches benefited more from home digital exposure in this domain. These findings highlight that digital device access alone is not sufficient for literacy development. Children’s motivational and strategic dispositions shape how digital resources are translated into digital literacy development. Effective approaches to supporting early digital literacy should integrate both access to digital tools and opportunities to foster motivation, curiosity, and self-regulation in young learners.